Application Of Breathing Exercises to Increase Lung Capacity and Oxygen Saturation in The Elderly at Putra Mandiri Foundation Gorontalo City - Suwarni Loleh; Yusrin Aswad; Lisdiyanti Usman (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
With Increasing Age, There Is A Decrease In Physiological Functions In Organs, One Of Which Is The Respiratory Organ. According To (Pangestuti Et Al., 2015), That Breathing Exercises Using The Diaphragm Muscle Can Provide A Large Space For Lung Development So As To Increase The Strength Of The Respiratory Muscles. This Community Service Activity Aims To Implement Breathing Exercises As An Effort To Increase Oxygen Saturation (Sao2) And Lung Capacity In The Elderly. The Targets Of This Community Service Are The Elderly Who Are At The Putra Mandiri Foundation, Gorontalo City. This Activity Is Carried Out In 3 Stages, Namely Simulation Of Breathing Exercises In The First And Second Stages, Monitoring And Evaluation In The Third Stage. The Results Of This Community Service Analysis Show A P Value (0.000) For An Increase In Sao2 And A P Value (0.03) For An Increase In Lung Capacity. Based On The Results Of The Analysis, It Can Be Concluded That There Is An Effect Of The Application Of Breathing Exercises On The Sao2 And Lung Capacity Of The Elderly. The Recommendation From This Community Service Is That Breathing Exercises Can Be Carried Out At The Posyandu For The Elderly At The Puskesmas And Become One Part Of Efforts To Prevent Lung Disease In The Elderly.